The Devil Doll - Merritt, Abraham 1884-1943 (Warner Archive Collection, 2024)
An escaped convict uses miniaturized humans to wreak vengeance on those who framed him. [imdb.de]
Original: USA, 1936
Bildformat: 1,37:1
Bonus: Kommentar von Filmhistoriker Dr. Steve Haberman und Filmhistoriker/Filmemacher Constantine Nasr, Cartoons Produzent: Leon Schlesinger "Milk and Honey" und "The Phantom Ship"
Keywords: Film; Blu-Ray-Disc